Relationship between Fair Values and Stock Price of Listed Firms in The Stock Exchange of Thailand - Watcharanukul, Krittapong (KKBS Journal of Business Administration and Accountancy, 2022)
The research aims to examine the relationship between fair values of investments in equity securities and stock price of listed firms in the Stock Exchange of Thailand. Totally, 174 firms were chosen as a sample of the study. Secondary data was gathered via SETSMART database. Descriptive statistics which were mean and standard deviation, and multiple regression analysis are employed for the data analysis. Independent variables consist of net income, cash flows from operating activities, fair value of investments in equity securities, level 1, level 2, and level 3 fair value of investments in equity securities. The dependent variable is stock price. The results show that net income, cash flows from operating activities, and fair value of investments in equity securities has positively related with stock price. In terms of fair value hierarchy, both of level 1 and level 2 fair value of investments in equity securities has positively related with stock price. Levels 3 fair value was not found